External quality assessment for arbovirus diagnostics in the World Health Organization Western Pacific Region, 2013–2016: improving laboratory quality over the years - Abdad, Mohammad Yazid; Squires, Raynal C; Cognat, Sebastien; Oxenford, Christopher John; Konings, Frank (Western Pacific Surveillance and Response, 2017)
Arboviruses continue to pose serious public health threats in the World Health Organization (WHO) Western Pacific Region. As such, laboratories need to be equipped for their accurate detection. In 2011, to ensure test proficiency, the WHO Regional Office for the Western Pacific piloted an external quality assessment (EQA) programme for arbovirus diagnostics. By 2016, it had grown into a global programme with participation of 96 laboratories worldwide, including 25 laboratories from 19 countries, territories and areas in the Region. The test performance of the 25 laboratories in the Region in 2016 was high with 23 (92%) reporting correct results in all specimens for dengue and chikungunya viruses. For Zika virus, 18 (72%) of the 25 laboratories reported correct results in all specimens, while seven (28%) demonstrated at least one error. When comparing iterations of this EQA programme in the Region between 2013 and 2016, the number of participating laboratories increased from 18 to 25. The first round only included dengue virus, while the latest round additionally included chikungunya, Zika and yellow fever viruses. Proficiency for molecular detection of dengue virus remained high (83–94%) over the four-year period. The observed proficiency for arbovirus diagnostics between 2013 and 2016 is an indicator of laboratory quality improvement in the Region.